Pemberdayaan Civitas Academika Dalam FKIP Expo Untuk Meningkatkan Mutu Pembelajaran - Misbah Fikrianto (CV. Multi Kreasi Media, 2024)
The implementation of the Tridharma of Higher Education is carried out holistically and sustainably. All processes carried out in the Tridharma of Higher Education support the achievement of learning objectives. The Faculty of Teacher Training and Education (FKIP) of Asy-syafi'iyah Islamic University carries out FKIP Expo activities as an effort to improve the quality of learning at the end of the semester, a place for alumni meetings, and to improve strategies for accepting new students. The implementation of the FKIP Expo provides enrichment from various aspects of education. This activity was attended by 97 students, 15 lecturers and 3 education staff. FKIP Expo activities consist of educational talk shows, exhibitions of works on technology and media subjects, predicted TOEFL tests, counseling services, artistic performances, and others. This activity presented three speakers, including: Rini Anita Putri, Nurul Hasanah Fajaria, and Shilmi. FKIP Expo activities involve the entire academic community including: Lecturers, Students and Education Staff. Achievement of learning quality in the Guidance and Counseling, English Language Education, and Master of Educational Technology study programs. Empowering the Academic Community at the FKIP Expo to improve the quality of learning. Based on the results of observations, 85% of participants stated that they were useful and satisfied with the FKIP EXPO activities The process of improving the quality of learning is a whole activity from learning planning, implementation, to learning assessment.